Palms and soles itchiness as a side effect of COVID-19 vaccination - Rehab Y. AL-Ansari; Mohammed Al-Sharari; Talal AL-Saadi (Elsevier, 2021)
Background: COVID-19 is a pandemic disease that has no definite treatment or preventive medication until late 2020 when vaccines were developed. Vaccines are a very useful new tool against COVID-19 that stimulate the immune system after recognition of viruses or their parts. Complications post vaccination could happen and they depend on the types, vaccine mechanism of action as well as some other patients' factors. Case report: We are reporting a 39 years old lady who is known as allergic to a strawberry and kiwi, otherwise medically free. She presented to the outpatient unit with a ten-days history of palms of the hands and soles of the feet itchiness that is associated with occasional redness after receiving the first dose of COVID-19 vaccination. There were no skin rashes or pruritis at any other sites. The patient was treated conservatively by antihistamine and the symptoms gradually resolved within five days. Conclusion: Allergic reaction is one of the expected complications post any COVID-19 or non-COVID-19 vaccination. Although the type, distributions and severity of allergic reactions are variable from person to another, yet isolated itching to palms and soles could be a rare side effect post first dose of COVID-19 vaccination (Pfizer-BioNTech) which is worth reporting. This presentation could be a type of allergic reaction which may require holding further doses, debate is there for further case reporting, research or evaluation.Learning points: • Isolated itching to palms and soles could be one of the side effects of COVID-19 vaccination (Pfizer-BioNTech) which is worth reporting.